Antiviral Activity against Avian Leucosis Virus Subgroup J of Degraded Polysaccharides from Ulva pertusa. (5th August 2018) - Sun, Yuhao; Chen, Xiaolin; Song, Lin; Liu, Song; Yu, Huahua; Wang, Xueqin; Qin, Yukun; Li, Pengcheng
Abstract : Avian Leukosis Virus Subgroup J (ALV-J), a retrovirus of avian, has caused enormous economics losses to poultry industry around the world. Polysaccharides from marine algae are featured diversity bioactivities. To find the potential effect to prevent ALV-J spread, in this study, polysaccharides from Ulva pertusa (UPPs) and four low molecular weight (Mw) U. pertusa polysaccharides (LUPPs) were prepared and their functions on ALV-J were investigated. Firstly, LUPPs were obtained by hydrogen peroxide (H 2 O 2 ) oxidative degradation. The effects of degradation conditions on Mw of the UPP were also investigated. Results showed that theH 2 O 2 oxidative degradation method could degrade UPP effectively, and the degradation was positively related toH 2 O 2 concentration and temperature and negatively to pH. The chemical characteristics of UPP and LUPPs were also determined. Afterwards, the anti-ALV-J activity of the polysaccharides were carried out in vitro. Results showed that UPP and LUPPs could inhibit ALV-J and LUPP-3 and Mw of 4.3 kDa exerted the strongest suppression. The action phase assay showed that LUPP-3 could bind with the viral particles and prevented ALV-J adsorption onto the host cells. And the ALV-J relative gene and gp85 protein expression were significantly suppressed after being administration with LUPP-3. Therefore, the low Mw polysaccharides from U. pertusa have great potential as an anti-ALV-J drug alternative.